Stochastic behavior of the coefficient of normal restitution - Gunkelmann, Nina; Montaine, Marina; Pöschel, Thorsten (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2014)
We consider the collision of a rough sphere with a plane by detailed analysis of the collision geometry. Using stochastic methods, the effective coefficient of restitution may be described as a fluctuating quantity whose probability density follows an asymmetric Laplace distribution. This result agrees with recent experiments by Montaine [Phys. Rev. E 84, 041306 (2011)]PLEEE81539-375510.1103/PhysRevE.84.041306. © 2014 American Physical Society.